NUMERICAL MODELING OF CONFINED MASONRY WALL RETROFITTED USING FERROCEMENT UNDER IN-PLANE CYCLIC LOADING - Susanto, Willy
This study focuses on developing a numerical model for retrofitted brick walls using ferrocement to assess their strength and behavior during earthquakes in Indonesia. The aim of this research is to develop a numerical model for retrofitted brick walls using LS-DYNA software, evaluate the impact of material parameters on the retrofitted brick wall model, and assess the behavior of retrofitted brick walls through parameters such as hysteresis curves and crack patterns. Analysis using LS-DYNA will be compared with experimental data to fill gaps in previous research on numerical modeling of brick masonry walls. This modeling evaluates the Concrete Damage Plastic Model (CDPM) to represent concrete, bricks, and mortar, as well as explores micro modeling details in analyzing the behavior of brick walls with ferrocement. The analysis results indicate that while numerical models provide a fairly accurate representation of structural behavior, there are significant differences between simulation and experimental results. Numerical models tend to produce lower stiffness degradation and higher energy dissipation rates compared to experimental testing, indicating that complex phenomena such as pinching are difficult to replicate in ideal numerical simulations. Factors such as material imperfections, variations in test conditions, and complex interactions between structural components are challenging to accurately model, emphasizing the importance of careful interpretation of numerical model results. Numerical modeling also shows that the ferrocement layer enhances the structural stiffness but may conceal internal damage such as cracks between bricks and mortar, as well as potential buckling out of plane. Both phenomena contribute to extreme pinching in the test specimens. The contact base method is applied to improve model accuracy, but still does not fully succeed in modeling the pronounced pinching phenomenon.